MMIC design for a 5.8 GHz receiver front-end - Low, Eng Chuan. (2008)
In this project, the design of receiver front-ends (RFEs) were investigated at microwave frequency of 5.8 GHz by using the GaAs technology. The RFE system consists of a low-noise amplifier (LNA) and a mixer. The LNA can either be a single-stage LNA or a two-stage LNAs (in which 2 single-stage LNAs are cascaded in series). A theoretical discussion of these LNAs (single-stage and dual-stage LNA) are presented in this report. The mixer can either be a single-gate FET mixer or a dual-gate FET mixer. Again, a theoretical discussion of these mixer topologies are presented in this report. The RFE system forms part of a larger system for a commercial wireless application. The software used in designing this system is Hewlett-Packard Microwave Design System (HP-MDS). The MESFET model used throughout the design phase is HP EEFET3. Extraction of this model parameters was carried out using IC-CAP. The design phase of this RFE consists of MDS simulation which is divided into three parts : (a) discrete components simulation (b) distributed component simulation (c) layout simulation.